IMPLEMENTASI SENAM DIABETIK PADA PENDERITA DIABETES MELLITUS DI DESA SOBONTORO KECAMATAN TAMBAKBOYO - Tiara Putri Ryandini; Mokhamad Nurhadi; Lukman Hakim; Mei Widyawati (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2021)
Diabetes Mellitus is a group of metabolic diseases characterized by hyperglycemia that occurs due to abnormalities in insulin secretion, insulin action, or both. This activity was carried out in the village of Sobontoro Tambakboyo on May 27, 2020, attended by 20 people. This activity is carried out in 3 stages, namely the preparation, implementation, and completion stages. Diabetes Mellitus is a chronic disease that causes multi-system disorders and is characterized by hyperglycemia caused by insulin deficiency or inadequate insulin action. The people of Sobontoro Tambakboyo village tend not to pay attention to a healthy lifestyle in terms of choosing food but after being given Health Education the community understands more about the concept of lifestyle for people with Diabetes Mellitus and to prevent Diabetes Mellitus.